Pekka Poikanen (Peter Pan) - Barrie, J. M. (James Matthew), 1860-1937; Tuulio, Tyyni, 1892-1991 (Salt Lake City, UT : Project Gutenberg, 2015)
"Pekka Poikanen (Peter Pan)" by J. M. Barrie is a work originating as a play in 1904 and a novel in 1911. It follows Peter Pan, a mischievous boy who can fly and never grows up, as he takes Wendy Darling and her brothers to Neverland$1 (Ba magical island filled with mermaids, fairies, pirates, and the Lost Boys. Together they face adventures involving the jealous fairy Tinker Bell and the villainous Captain Hook, while Wendy becomes a mother figure to Peter's gang of lost children. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Peter_and_Wendy Wikipedia page about this book: https://fi.wikipedia.org/wiki/Peter_Pan
Release date is 2015-03-08
Produced by Juha Kiuru
Keywords: Fantasy literature; Peter Pan (Fictitious character) -- Fiction; Never-Never Land (Imaginary place) -- Fiction; Pirates -- Fiction; Fairies -- Fiction